(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Liver cirrhosis is a chronic, progressive liver disease characterized by diffuse fibrosis, regenerative nodule formation, and distortion of normal hepatic architecture. It represents the final stage of many chronic liver disorders and is associated with high morbidity and mortality worldwide. This study analyzes the etiology, pathogenesis, clinical manifestations, diagnostic approaches, complications, and contemporary management strategies of liver cirrhosis using the IMRAD structure and evidence-based guidelines.